Nematicidal Activity of Phytochemicals against the Root-Lesion Nematode Pratylenchus penetrans - Pedro Barbosa; Jorge M. S. Faria; Tomás Cavaco; Ana Cristina Figueiredo; Manuel Mota; Cláudia S. L. Vicente (Plants, 2024)
Plant-parasitic nematodes (PPNs) are highly damaging pests responsible for heavy losses in worldwide productivity in a significant number of important plant crops. Common pest management strategies rely on the use of synthetic chemical nematicides, which have led to serious concerns regarding their impacts on human health and the environment. Plant natural products, or phytochemicals, can provide a good source of agents for sustainable control of PPNs, due to their intrinsic characteristics such as higher biodegradability, generally low toxicity for mammals, and lower bioaccumulation in the environment. In this work, the nematicidal activity of 39 phytochemicals was determined against the root-lesion nematode (RLN) Pratylenchus penetrans using standard direct and indirect contact methodologies. Overall, the RLN was tolerant to the tested phytochemicals at the highest concentration, 2 mg/mL, seldom reaching full mortality. However, high activities were obtained for benzaldehyde, carvacrol, 3-octanol, and thymol, in comparison to other phytochemicals or the synthetic nematicide oxamyl. These phytochemicals were seen to damage nematode internal tissues but not its cuticle shape. Also, the environmental and (eco)toxicological parameters reported for these compounds suggest lower toxicity and higher safety of use than oxamyl. These compounds appear to be good candidates for the development of biopesticides for a more sustainable pest management strategy.